THE EFFICACY OF USING SVF AND BMAC TO TREAT POST-COVID AVASCULAR NECROSIS OF THE FEMORAL HEAD - S.U. Asilova; A.B. Mirzaev; M. Salomov (Central Asian Journal of Medicine, 2023)
Avascular necrosis of the femoral head (ANFH) is a complex condition recently associated with the coronavirus pandemic. It predominantly affects working-age men, increasing the risk of early joint failure and subsequent revision after total hip replacement. A crucial aim in modern orthopedics is to delay end-stage necrosis to avoid early joint replacement surgeries. This study, conducted at the Akfa Medline clinic, presents outcomes from employing cell therapy decompression in 36 post-coronavirus infection ANFH patients. Study criteria included patients in ARCO stages 1 and 2, aged 18 to 65 years, excluding cases from post-traumatic avascular necrosis, alcohol-related avascular necrosis, or those associated with rheumatoid diseases and steroid use. Procedures involved cellular material collection, femoral head decompression, and cellular material introduction into the necrotic area. Clinical data analysis, including the Harris Hip Score (HHS) and Visual Analog Scale (VAS), demonstrated significant patient improvement. MRI studies confirmed structural hip joint changes, reduced swelling, and synovitis regression. The study concludes that femoral head decompression combined with cell transplantation like PRP, BMAC, and SVF is a safe and effective treatment for early-stage avascular necrosis of the femoral head. This technique has successfully reduced femoral head collapse rates and may delay or prevent the need for total hip arthroplasty.